Baicalein Ameliorates Aβ-Induced Memory Deficits and Neuronal Atrophy via Inhibition of PDE2 and PDE4 - Shi, Jing; Li, Yuanyuan; Zhang, Yi; Chen, Jie; Gao, Jianqing; Zhang, Tianyuan; Shang, Xiaoguang; Zhang, Xiangnan (Frontiers in Pharmacology, 2021)
Inhibition of phosphodiesterase 2 and 4 (PDE2A and PDE4) increases the intracellular cAMP and/or cGMP levels, which may prevent Amyloid β 42 oligomers (Aβ) related cognitive impairment and dementias. Baicalein, one of natural flavones found in the root of Scutellaria baicalensis Georgi, has a wide range of pharmacological activities including antioxidant and anti-inflammatory effects. However, no studies suggest whether baicalein mediated anti-Alzheimer’s disease (AD) events involve PDEs subtypes-mediated neuroprotective pathways. The present study examined whether memory enhancing effects of baicalein on Aβ- induced cognitive impairment are related to regulating neuroplasticity via PDE2 and PDE4 subtypes dependent cAMP/cGMP neuroprotective pathway. The results suggested that microinjected of Aβ into CA1 of hippocampus induced cognitive and memory impairment in mice, as evidenced by decreased recognition index in the novel object recognition (NOR) task, impaired memory acquisition, retention and retrieval in the Morris water maze (MWM) and shuttle box tests. These effects were reversed by treatment with baicalein for 14 days. Moreover, Aβ-induced neuronal atrophy and decreased expression of two synaptic proteins, synaptophysin and PSD 95, were prevented by baicalein. The increased expression of PDE2A and PDE4 subtypes (PDE4A, PDE4B and PDE4D), and decreased levels of cAMP/cGMP, pCREB/CREB and BDNF induced by Aβ were also blocked by chronic treatment of baicalein for 14 days. These findings suggest that baicalein’s reversal of Aβ-induced memory and cognitive disorder may involve the regulation of neuronal remodeling via regulation of PDE2/PDE4 subtypes related cAMP/cGMP -pCREB-BDNF pathway.